HUBUNGAN ANTARA KADAR GLUKOSA DARAH DENGAN TEKANAN DARAH PADA LANSIA DI UPT PSTW BONDOWOSO - Muhammad Amin; Faridha Puspitasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2016)
The elderly often experience high blood glucose levels and high blood pressure. Based on a preliminary study conducted with 30 elderly people at UPT PSTW Bondowoso (73%) elderly who have high blood pressure. One effort to control blood pressure is to control several factors that affect blood pressure, one of which is blood glucose levels. The purpose of this study was to determine the relationship between blood glucose levels and blood pressure in the elderly at UPT PSTW Bondowoso. Analytical survey research methods with cross sectional approach. The sample in this study were 60 elderly using probability sampling techniques with a simple random sampling approach. Data analysis used Pearson correlation and 95% confidence level (α ≤ 0.05) with a significance level of 0.00. The results showed that there was a relationship between blood glucose levels and blood pressure. The conclusion of this study is that when a person has high blood glucose levels, that person will tend to have high blood pressure and it can be concluded that there is a relationship between blood glucose levels and blood pressure in the elderly in UPT PSTW Bondowoso. It is recommended to the elderly to control blood glucose levels so that it does not negatively impact blood pressure, especially in the elderly